Method for evaluating cleanliness of zirconium-based amorphous alloy
By using the inert gas melting infrared analysis method to release oxygen in a step-by-step manner and calculate the cleanliness index I, the problem of rapid and accurate evaluation of the cleanliness of zirconium-based amorphous alloys was solved, achieving efficient and accurate alloy cleanliness evaluation and reducing production costs.
Patent Information
- Application Number
- CN202511173855.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-08-21
AI Technical Summary
Existing technologies make it difficult to quickly and accurately evaluate the cleanliness of zirconium-based amorphous alloys, resulting in Y2O3 inclusions in the alloy affecting mechanical properties and corrosion resistance. Existing methods are complex and time-consuming.
The inert gas melting infrared analysis method is used to perform step-by-step heating to release the matrix oxygen and oxide oxygen in the zirconium-based amorphous alloy in stages. The cleanliness is evaluated by calculating the cleanliness index I = wOy/ wOt.
It achieves fast and accurate cleanliness evaluation of zirconium-based amorphous alloys, reduces the evaluation time of master alloy grades by 70%, improves the evaluation accuracy to 97%, reduces production costs and improves product yield.
Smart Images

Figure CN120721670A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material smelting and casting, and particularly relates to a method for evaluating the cleanliness of a zirconium-based amorphous alloy. Background Art
[0002] As we all know, compared with traditional metal materials, amorphous alloys have unique advantages such as high strength, high elasticity, excellent corrosion resistance and good forming ability. They have been widely used in many fields such as electronics, machinery and medical equipment.
[0003] However, due to the increasing oxygen content of industrial raw materials and the uncontrollable oxygenation during the production process, the forming ability and mechanical properties of amorphous alloys have dropped sharply. Therefore, when smelting amorphous master alloys under industrial conditions, rare earth element Y is usually added as a scavenger to reduce the oxygen content of the alloy. Y element is added to the alloy as a scavenger in a certain proportion. Although it plays a role in preventing the alloy from being oxygenated and compensating for the problem of reduced amorphous forming ability due to the high oxygen content of the alloy, due to the oxygen absorption effect, a large amount of Y2O3 inclusions are formed, enriched into slag and enter the master alloy, which has a serious impact on the cleanliness of the master alloy. Amorphous alloy products containing Y2O3 inclusions will have defects such as pores or local crystallization inside, which have a significant negative effect on the mechanical properties and corrosion resistance of the product. Therefore, in industrial production, it is very necessary to quickly evaluate the cleanliness of zirconium-based amorphous master alloys and amorphous alloy products.
[0004] Currently, the cleanliness of zirconium-based amorphous alloys is typically evaluated by analyzing the total oxygen content of the alloy and verifying the maximum critical amorphous size (Dmax). The conventional inert gas melting-infrared absorption analysis method utilizes a rapid heating program, releasing all forms of oxygen in the sample within a short period of time (approximately 30 seconds). The oxygen release curve, consisting of overlapping oxygen release peaks from different states, forms a single peak, reflecting the total oxygen content of the sample. However, this method suffers from significant error. Verifying the maximum critical amorphous size, while more accurate, requires preparing the master alloy into round rods using electric arc furnace melting and vacuum casting. The amorphous nature of alloy samples of varying sizes is then verified using XRD or DSC. The sample preparation process is complex and time-consuming, resulting in a long verification cycle. Summary of the Invention
[0005] Therefore, the present invention provides a method for evaluating the cleanliness of zirconium-based amorphous alloys, the main purpose of which is to provide a simple, fast, and error-free method for evaluating the cleanliness of zirconium-based amorphous alloys.
[0006] In order to solve the above problems, the present invention provides a method for evaluating the cleanliness of a zirconium-based amorphous alloy, comprising the following steps: Step 1): Determine the oxygen content in the zirconium-based amorphous alloy by inert gas melting infrared analysis to obtain the content of oxygen in different forms in the zirconium-based amorphous alloy; Wherein, the inert gas melting infrared analysis method adopts a step-by-step heating method; Step 2): Calculate the cleanliness index of the zirconium-based amorphous alloy according to the oxygen content in the different existence forms.
[0007] Furthermore, in step 1), the stepwise heating includes: The first heating stage: heating to the first set temperature and keeping it warm for the first set time; Second heating stage: heating to the second set temperature and keeping warm for the second set time.
[0008] Furthermore, the first set temperature and the second set temperature are controlled by adjusting the heating power; Among them, the heating power of the first heating stage is 2500-3000w; the first set temperature is 1400-1600℃; the first set time is 60-80s; the heating power of the second heating stage is 5000-6000w, the second set temperature is 2100-2300℃; the second set time is 40-60s.
[0009] Furthermore, the oxygen in different forms includes oxygen in the matrix and oxygen in the oxide; Among them, the content of matrix oxygen is w in mass percentage. O , the oxygen content in the oxide w Oy .
[0010] Furthermore, the calculation formula of the cleanliness index of the zirconium-based amorphous alloy is: I = w Oy / w Ot ; Among them, w Oy is the oxygen content in the oxide, w Ot is the matrix oxygen content w O The oxygen content in the oxide w Oy sum.
[0011] Furthermore, in the step 1), the zirconium-based amorphous alloy is a granular zirconium-based amorphous alloy.
[0012] Furthermore, the diameter of the granular zirconium-based amorphous alloy is 3-5 mm; the weight of the granular zirconium-based amorphous alloy is 0.05-0.15 g.
[0013] Furthermore, samples are taken from the upper, middle and lower parts of the zirconium-based amorphous alloy master alloy ingot or the zirconium-based amorphous alloy piece, and the granular zirconium-based amorphous alloy is obtained by cutting and grinding after sampling.
[0014] Furthermore, in the step 1), the zirconium-based amorphous alloy is a zirconium-based amorphous alloy containing a rare earth element; preferably, the rare earth element is Y.
[0015] Furthermore, in step 1), the inert gas fusion infrared analysis method uses an oxygen, nitrogen, and hydrogen analyzer; the analysis crucible used in the inert gas fusion infrared analysis method is a graphite-jacketed crucible; and the co-solvent used in the inert gas fusion infrared analysis method is a nickel basket.
[0016] The method for evaluating the cleanliness of zirconium-based amorphous alloys provided by the present invention has the following beneficial effects: 1. The method for evaluating the cleanliness of a zirconium-based amorphous alloy provided by the present invention comprises the following steps: using an inert gas melting infrared analysis method to determine the oxygen content in the zirconium-based amorphous alloy to obtain the content of oxygen in different forms in the zirconium-based amorphous alloy; wherein the inert gas melting infrared analysis method adopts a step-by-step heating method; and then calculating the cleanliness index of the zirconium-based amorphous alloy based on the oxygen content in different forms. It should be noted that the inert gas melting infrared analysis method is used for measurement, which does not require complicated sample preparation and long-term verification, and is simple and fast to operate; and the step-by-step heating method is used to release oxygen in different forms in the zirconium-based amorphous alloy in stages, obtaining a completely separated multi-peak oxygen release spectrum, analyzing the specific form and corresponding content of oxygen based on the obtained oxygen release spectrum, and thus calculating the cleanliness index based on the oxygen content in different forms in the alloy.
[0017] 2. Furthermore, the step-by-step heating includes: a first heating stage: heating to a first set temperature and keeping it warm for a first set time, so that the zirconium-based amorphous alloy is initially melted and part of the existing oxygen (i.e., matrix oxygen) is released; a second heating stage: heating to a second set temperature and keeping it warm for a second set time; so that the zirconium-based amorphous alloy is completely melted and the residual oxygen is released.
[0018] 3. Furthermore, the alloy is processed into granular zirconium-based amorphous alloys during measurement. Granular samples have a larger specific surface area (surface area / volume), allowing for more complete contact with the heat source during melting, accelerating the conversion of internal oxygen into gas. This prevents incomplete oxygen release from incomplete melting, which can lead to measurement errors. However, if the sample diameter and weight are too small, it may vaporize quickly, resulting in an oxygen escape rate too high to be accurately captured by the infrared detector. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the description of the prior art. The drawings described below are merely exemplary. Those skilled in the art can, without inventive effort, derive other implementation drawings based on the provided drawings.
[0020] Figure 1 (a) and 1(b) are the microscopic distribution diagrams of Y2O3 and the precipitation position distribution diagrams of the crystal phase in the zirconium-based amorphous alloy containing Y element; Figure 2 (a) and 2(b) are comparative diagrams of oxygen release forms in the zirconium-based amorphous alloys obtained in Comparative Example 1 and Example 1 of the present invention, respectively; Figures 3(a) and 3(b) are the XRD peak comparison diagrams of the zirconium-based amorphous alloy sample and the crystal sample, respectively; Figure 4 shows the cleanliness index of zirconium-based amorphous alloy I , the corresponding relationship between the total oxygen content of the alloy and the forming ability of the alloy. DETAILED DESCRIPTION
[0021] To further illustrate the technical means and effects employed by the present invention to achieve its intended objectives, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention is provided in conjunction with the accompanying drawings and preferred embodiments. In the following description, different references to "one embodiment" or "embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics of one or more embodiments may be combined in any suitable manner.
[0022] The total oxygen content of the zirconium-based amorphous alloy containing Y element consists of two parts: matrix oxygen (O) in the alloy matrix and oxygen in the slag. The matrix oxygen exists in atomic state as one of the components of the alloy, while the oxygen in the slag is generated during the smelting process of the amorphous alloy master alloy and is Y2O3. The production process of amorphous alloy products requires a rapid cooling process to avoid the precipitation of crystalline phases in the alloy. During the rapid cooling process, due to the relatively large size of Y2O3 inclusions, such as Figure 1 As shown in (a), non-uniform nucleation occurs around Y2O3, causing crystals to precipitate around the inclusions, such as Figure 1 As shown in (b), this leads to a decrease in the amorphous forming ability of the master alloy, poor mechanical properties, and low yield of amorphous products.
[0023] Therefore, this invention first builds on the traditional inert gas melting infrared absorption method and, based on the metallurgical thermodynamics theory of isothermal carbothermal reduction reactions, establishes a two-step, stepped heating program based on the different release temperatures of different types of oxygen. This allows for simultaneous analysis of both matrix oxygen (O) and slag oxygen (Y2O3) in (Y-containing) zirconium-based amorphous master alloys and products. Secondly, a cleanliness evaluation method for zirconium-based amorphous alloys and products is established using two indicators: the total oxygen content (w(Ot)) in the alloy and the oxygen content (w(Oy)) in the slag. The specific scheme is as follows: The present invention provides a method for evaluating the cleanliness of a zirconium-based amorphous alloy, comprising the following steps: Step 1): Place the zirconium-based amorphous alloy sample containing Y element and the flux in a graphite sleeve crucible, and then use an oxygen, nitrogen and hydrogen analyzer to perform inert gas melting infrared analysis, so that the zirconium-based amorphous alloy sample containing Y element is heated to a first set temperature and kept warm for a first set time to allow the sample to initially melt and release part of the existing oxygen (matrix oxygen), and then heat it to a second set temperature and keep warm for a second set time to allow the sample to completely melt and release residual oxygen, obtaining a completely separated bimodal oxygen release spectrum, thereby obtaining the matrix oxygen content w O , the content of oxygen in oxides (oxygen in slag) w Oy ; The first and second set temperatures are controlled by adjusting the heating power. The heating power in the first heating stage is 2500-3000W, the first set temperature is 1400-1600°C, and the first set time is 60-80s. The heating power in the second heating stage is 5000-6000W, the second set temperature is 2100-2300°C, and the second set time is 40-60s. The co-solvent is a nickel basket. Preferably, 0.1g of the sample (granular zirconium-based amorphous alloy) is weighed, cleaned, and then wrapped with approximately 1g of the nickel basket.
[0024] Step 2): Calculate the cleanliness index of zirconium-based amorphous alloy according to the oxygen content in different forms. The corresponding calculation formula is: Cleanliness index of zirconium-based amorphous alloy I = w Oy / w Ot ; Among them, w Ot is the matrix oxygen content w O The oxygen content in the oxide w Oy sum.
[0025] It should be noted that the inert gas fusion infrared analysis method is simple and rapid, eliminating the need for complex sample preparation and lengthy validation cycles. Furthermore, a stepwise heating method is employed to gradually release the different oxygen forms in the zirconium-based amorphous alloy, resulting in a completely separated multi-peak oxygen release spectrum. The resulting oxygen release spectrum is then used to analyze the specific oxygen forms and corresponding contents, allowing the cleanliness index to be calculated based on the oxygen contents of the different forms in the alloy. This method excels in distinguishing between different oxygen forms in alloys and is suitable for analyzing the forms and contents of oxide impurities in zirconium-based amorphous master alloys and products.
[0026] In the first heating stage, at a heating power of 2500-3000W, the matrix oxygen release temperature is 1400-1600°C. Holding at this heating power and temperature for 60-80 seconds in the first heating stage ensures complete matrix oxygen release and prevents oxygen release from the Y2O3 oxide. In the second heating stage, at a heating power of 5000-6000W, the Y2O3 oxygen release temperature is 2100-2300°C. Holding at this heating power and temperature for 40-60 seconds in the second heating stage ensures that the Y2O3 oxygen release temperature is maintained.
[0027] The method of the present invention is particularly simple and highly practical, and can efficiently and accurately evaluate the technical issues of the cleanliness of Y-containing zirconium-based amorphous alloys and products in the industry. On the one hand, compared with the existing evaluation method that evaluates the cleanliness of the alloy by verifying the maximum amorphous critical size (Dmax), the use of the present invention can reduce the time for evaluating the master alloy grade by 70%, thereby reducing production costs. On the other hand, compared with the existing evaluation method that only uses a single total oxygen content w Ot Compared with the evaluation of alloy cleanliness by using w(Ot) , the evaluation accuracy can be increased from 80% to 97% after using the present invention, which can achieve the goal of improving product yield.
[0028] After the cleanliness of the master alloy is evaluated using the method of the present application, the amorphous master alloy ingots or products with low cleanliness can be returned to the furnace for remelting and purification. The purity of the alloy can be improved by adding Y element to reduce oxygen and removing slag by skimming, so that the alloy can be recycled, thereby achieving the goal of reducing production costs and improving product yield.
[0029] In some embodiments, before step 1), the method further includes taking samples from the top, middle, and bottom of the zirconium-based amorphous alloy master alloy ingot or product (zirconium-based amorphous alloy part), and then cutting and polishing the samples to obtain zirconium-based amorphous alloy granules. Preferably, the diameter of the zirconium-based amorphous alloy granules is 3-5 mm, and the weight of the zirconium-based amorphous alloy granules is 0.1 g. Taking samples at different locations ensures more accurate data.
[0030] Granular samples have a larger specific surface area (surface area / volume), which allows for more sufficient contact with the heating source during sample melting, a faster rate of conversion of internal oxygen elements into gases, and avoids incomplete melting inside the sample resulting in incomplete oxygen release and causing errors in measurement results. However, if the diameter and weight of the sample are too small, it may be rapidly vaporized, leading to too fast an oxygen escape rate and being unable to be accurately captured by the infrared detector.
[0031] It should be noted that different types of oxides, including Fe2O3, MnO2, NiO, CuO, SiO2, Al2O3, and rare earth oxides such as Y2O3, La2O3, and CeO2, have different decomposition temperatures (oxygen release temperatures), and their decomposition temperature order is: CuO < Fe2O3 < NiO < MnO2 < SiO2 < Al2O3 < Y2O3. According to the changes in the atmosphere and pressure conditions inside the crucible during the analysis process of inert gas fusion infrared analysis, the initial release temperatures of matrix oxygen (O) and oxygen in oxides (Y2O3, La2O3, CeO2, etc.) in the zirconium-based amorphous alloy containing rare earth elements under this condition are theoretically calculated. The carbon thermal reduction reaction equation and Gibbs free energy calculation formula of the oxide under equilibrium conditions are as follows: ZxOy(s) + yC(g) = xZ + yCO(g) △G = △G Ɵ + RTlnK K = ( a z x p Co y ) / ( a c y a ZxOy ) In the formula: K is the equilibrium constant, a c y 、 a z x 、 a ZxOy are the activities of carbon, oxide, and reduction product respectively, [[ID=A]] p [[ID=B]] Co is the partial pressure of Co. By calculating △G = 0 TThe starting temperature of the reaction is determined by the value of γ-Y. That is, the starting temperature of oxygen release in the matrix and the oxide. The calculated results show that the starting temperature of oxygen release in the matrix of the Y-containing zirconium-based amorphous alloy is 1500°C, and the releasing temperature of oxygen in the oxide is 2200°C.
[0032] Due to the extremely high reactivity of rare earth elements (REs), their ability to bind oxygen is far greater than that of elements such as Al, Ni, and Cu. Consequently, the oxide species present in rare earth zirconium-based amorphous alloys are limited, primarily rare earth yttrium oxides and a small amount of matrix oxygen. Therefore, a simple two-stage heating method can be used to completely distinguish between the two forms of oxygen. Compared to other alloys with a wider range of oxide types, the two-stage heating method is more suitable for rare earth zirconium-based amorphous alloys, effectively avoiding interference from other oxide species and thus achieving more accurate oxygen content analysis results.
[0033] In addition, due to the high stability of rare earth oxides, the release of oxygen in rare earth oxides during the oxygen content detection process needs to reach a higher temperature condition. The release temperature difference between matrix oxygen and oxygen in oxides is about 700°C. Therefore, when designing the heating program, the heating power of the two heating processes is quite different. This temperature difference can ensure that under the first set temperature condition, the matrix oxygen begins to be released while the oxygen in the oxide does not begin to be released, and under the second set temperature condition, the matrix oxygen has been completely released and the oxygen in the oxide has just begun to be released, thereby achieving the goal of completely separating and measuring the two forms of oxygen.
[0034] The present invention is further described below with reference to specific examples and comparative examples.
[0035] In the Examples and Comparative Examples, the cleanliness levels of six different batches of Y-containing zirconium-based amorphous master alloys were determined. Specifically, the alloy system was Zr-Cu-Ni-Al-Ti-Y. Because each batch varied in raw materials, impurity content, oxygen content, and worker handling techniques, the glass-forming abilities of the four amorphous alloys varied significantly. Therefore, the six batches were designated Master Alloy Samples 1-6. Master alloys with the same number in the Examples and Comparative Examples represent samples from the same batch.
[0036] Example 1 This embodiment provides a method for evaluating the cleanliness of a zirconium-based amorphous alloy, which specifically includes the following steps: Step 1): Take samples from the upper and lower parts of the master alloy samples No. 1-6 respectively, process them into granular test specimens with a smooth surface, and the sample weight is about 0.1g. Use alcohol ultrasonic cleaning for 3 minutes, blow dry on the test paper for later use; Then, the Y-containing zirconium-based amorphous alloy sample and the flux nickel basket are placed in a graphite sleeve crucible, and then an oxygen, nitrogen, and hydrogen analyzer is used to perform an inert gas melting infrared analysis method. The Y-containing zirconium-based amorphous alloy sample is heated to a first set temperature and kept warm for a first set time, and then heated to a second set temperature and kept warm for a second set time to obtain a completely separated bimodal oxygen release spectrum, which is as shown in FIG. Figure 2 (b) shows; in this spectrum, the matrix oxygen content w O and the oxygen content in oxides (oxygen in slag) w Oy ; Among them, the first set temperature and the second set temperature are controlled by adjusting the heating power; among them, the heating power of the first heating stage is 2750w, the first set temperature is 1500℃; the first set time is 70s; the heating power of the second heating stage is 5500w, the second set temperature is 2200℃; the second set time is 50s.
[0037] Step 2): According to the oxygen content of the matrix w O and the oxygen content in oxides (oxygen in slag) w Oy Calculate the cleanliness index of zirconium-based amorphous alloy. The corresponding calculation formula is: Cleanliness index of zirconium-based amorphous alloy I = w Oy / w Ot ; Among them, w Ot is the matrix oxygen content w O The oxygen content in the oxide w Oy sum.
[0038] The oxygen content and grade evaluation results obtained in this example are shown in Table 1.
[0039] Table 1 Oxygen content and grade evaluation results of master alloys No. 1-6
[0040] The rating standard of Y-containing zirconium-based amorphous master alloy is: when the total oxygen content of the alloy is w Ot When the total oxygen content of the alloy is less than 400ppm, the alloy is rated as Class A; when the total oxygen content of the alloy is w Ot When the total oxygen content of the alloy is between 400ppm and 800ppm, the cleanliness index based on the method of this application is adopted. I To grade the master alloy, I When ≤0.5, the alloy is rated as Class B. I When the value is greater than 0.5, the alloy is rated as Class C. Therefore, the rating types of master alloys No. 1-6 are: Master alloy No. 1 is Class A, Master alloys No. 2-3 are Class B, Master alloys No. 4-5 are Class C, and Master alloy No. 6 is Class D.
[0041] Comparative Example 1 This comparative example provides a method for evaluating the cleanliness of a zirconium-based amorphous alloy, which specifically includes the following steps: Step 1): Take samples from the upper and lower parts of the master alloy samples No. 1-6 respectively, process them into granular test specimens with a smooth surface, and the sample weight is about 0.1g. Use alcohol ultrasonic cleaning for 3 minutes, blow dry on the test paper for later use; Then the Y-containing zirconium-based amorphous alloy sample and the flux nickel basket are placed in a graphite sleeve crucible, and then an oxygen, nitrogen and hydrogen analyzer is used to perform an inert gas melting infrared analysis method. The Y-containing zirconium-based amorphous alloy sample is directly heated to a set temperature and kept at this temperature for a set time to obtain a single peak oxygen release spectrum. The spectrum is as shown in FIG. Figure 2 (a) shows; in this spectrum, the matrix oxygen content w O and the oxygen content in oxides (oxygen in slag) w Oy ; Among them, the set temperature is controlled by adjusting the heating power; the heating power corresponding to the above-mentioned approved temperature is 5500w; the set time is 45s.
[0042] Step 2): The cleanliness grade of the alloy was evaluated based on the total oxygen content in the master alloy sample. The results are shown in Table 2.
[0043] Table 2 Total oxygen content and grade evaluation results of master alloys No. 1-6
[0044] The standard for rating the purity level of alloys by using the total oxygen content method is: when the total oxygen content of the alloy is w Ot When the total oxygen content of the alloy is 400ppm<w Ot When the total oxygen content of the alloy is 600ppm<w Ot When the total oxygen content of the alloy is less than 800ppm, the alloy is classified as Class C; when the total oxygen content of the alloy is w Ot When the content is greater than 800ppm, the alloy is rated as Class D. Therefore, the rating types of master alloys No. 1-6 are: Master alloy No. 1 is Class A, Master alloys No. 2 and No. 5 are Class B, Master alloys No. 3 and No. 4 are Class C, and Master alloy No. 6 is Class D.
[0045] Comparative Example 2 This comparative example provides a method for evaluating the cleanliness of a zirconium-based amorphous alloy, which specifically includes the following steps: Step 1): Take samples from the upper and lower parts of the master alloy samples No. 1-6, with a sample weight of 80-100g, clean them with alcohol ultrasonically for 3 minutes, and blow dry them on the test paper for later use; Step 2): The alloy sample is prepared into a rod-shaped sample with a diameter of Φ14 mm by vacuum casting. The equipment used is the arc melting system AM-200 (EB). The specific steps are as follows: the alloy is placed in a crucible in a vacuum arc furnace, and after the vacuum is evacuated to 5 Pa, 0.4 Pa of protective gas Ar gas is injected; under protective atmosphere conditions, the alloy is remelted by arc melting. After repeated melting 3 times, the alloy melt is quickly flipped and cast into a copper mold. After the alloy cools, the test rod-shaped sample is taken out. The preparation time of each sample is about 1 hour; Step 3): Cut the rod-shaped sample of alloy No. 1-6 2 cm from the bottom to expose the cross section, grind the cross section with 2000 grit sandpaper, clean it, and then perform XRD analysis. The peak shape of the XRD result determines whether the rod-shaped alloy sample is amorphous, such as Figure 3 The results are as follows: among the Φ14mm rod specimens of master alloys 1-6, only alloy 1 is amorphous, so the amorphous forming ability of master alloy 1, that is, Dmax≥Φ14mm; Step 4): Master alloys 2-6 were vacuum cast into rods with a diameter of 12 mm. Steps 2) and 3) were repeated to verify that the 12 mm rods were amorphous. Similarly, the Dmax values of alloys 1-6 were verified. The results are shown in Table 3.
[0046] Table 3 Glass forming ability (D max ) and grade evaluation results
[0047] The rating standard for the maximum amorphous critical size method (Dmax) is: when the alloy's amorphous forming ability Dmax>Φ12mm, the alloy is rated as Class A; when the alloy's amorphous forming ability is Φ10mm≤Dmax≤Φ12mm, the alloy is rated as Class B; when the alloy's amorphous forming ability is Φ8mm≤Dmax<Φ10mm, the alloy is rated as Class C; when the alloy's amorphous forming ability Dmax<Φ8mm, the alloy is rated as Class D. Therefore, the rating types of master alloys No. 1-6 are: Master alloy No. 1 is Class A, master alloys No. 2-3 are Class B, master alloys No. 4-5 are Class C, and master alloy No. 6 is Class D.
[0048] It should be noted that: the alloy cleanliness index in Example 1 I , the total oxygen content of the alloy in Comparative Example 1 w Ot , and the corresponding relationship between the glass forming ability (Dmax) of the alloy in comparative example 2 is shown as follows. Among them, comparative example 2 is the currently commonly used zirconium-based amorphous master alloy rating method, and its evaluation results are stable and reliable with high accuracy. However, due to the tedious and complicated sample preparation and verification process, it is extremely time-consuming; comparative example 1 is the use of alloy total oxygen content w OtThe method is quick and simple to evaluate the alloy grade, but the total oxygen content w Ot There is no obvious corresponding relationship between the alloy's amorphous forming ability and the rating of alloys No. 3 and No. 5 is wrong, so the accuracy of this method is low; compared with Comparative Example 1, in the process of alloy oxygen content analysis, Example 1 specifically improves the heating process by adopting a two-step stepped heating process instead of the direct high-temperature heating method in the conventional method, which can accurately determine the oxygen content in the matrix and slag of the alloy. The evaluation results are consistent with the results of Comparative Example 2, and the cleanliness index I It is inversely proportional to the amorphous forming ability of the alloy, that is, as the cleanliness index I As the temperature increases, the amorphous forming ability of the alloy decreases. Therefore, this method is simple, fast and highly accurate, and is more suitable for the quality control link in the smelting and production process of zirconium-based amorphous alloys.
[0049] It is easy for those skilled in the art to understand that, under the premise of no conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.
[0050] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention. The above description is merely a preferred embodiment of the present invention. It should be noted that those skilled in the art can make various improvements and variations without departing from the technical principles of the present invention, and such improvements and variations shall also be considered within the scope of protection of the present invention.
Claims
1. A method for evaluating the cleanliness of a zirconium-based amorphous alloy, characterized in that: The following steps are involved: Step 1): Determine the oxygen content in the zirconium-based amorphous alloy by inert gas melting infrared analysis to obtain the content of oxygen in different forms in the zirconium-based amorphous alloy; Wherein, the inert gas melting infrared analysis method adopts a step-by-step heating method; Step 2): Calculate the cleanliness index of the zirconium-based amorphous alloy according to the oxygen content in the different existence forms.
2. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 1, characterized in that: In step 1), the stepwise heating includes: The first heating stage: heating to the first set temperature and keeping it warm for the first set time; Second heating stage: heating to the second set temperature and keeping warm for the second set time.
3. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 2, characterized in that: Controlling the first set temperature and the second set temperature by adjusting the heating power; Among them, the heating power of the first heating stage is 2500-3000w; the first set temperature is 1400-1600℃; the first set time is 60-80s; the heating power of the second heating stage is 5000-6000w, the second set temperature is 2100-2300℃; the second set time is 40-60s.
4. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 1, characterized in that: The oxygen in different existing forms includes oxygen in the matrix and oxygen in the oxide; Among them, the content of matrix oxygen is w in mass percentage. O , the oxygen content in the oxide w Oy .
5. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 4, characterized in that: The calculation formula of the cleanliness index of the zirconium-based amorphous alloy is: I = w Oy / w Ot ; Among them, w Oy is the oxygen content in the oxide, w Ot is the matrix oxygen content w O The oxygen content in the oxide w Oy sum.
6. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 1, characterized in that: In the step 1), the zirconium-based amorphous alloy is a granular zirconium-based amorphous alloy.
7. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 6, characterized in that: The diameter of the granular zirconium-based amorphous alloy is 3-5 mm; the weight of the granular zirconium-based amorphous alloy is 0.05-0.15 g.
8. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 6, characterized in that: Samples are taken from the upper, middle and lower parts of the zirconium-based amorphous alloy master alloy ingot or the zirconium-based amorphous alloy piece respectively, and then cut and polished to obtain the granular zirconium-based amorphous alloy.
9. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 1, characterized in that: In the step 1), the zirconium-based amorphous alloy is a zirconium-based amorphous alloy containing rare earth elements; Wherein, the rare earth element is Y.
10. The method for evaluating the cleanliness of zirconium-based amorphous alloy according to claim 1, wherein: In the step 1), the inert gas fusion infrared analysis method uses an oxygen, nitrogen and hydrogen analyzer; the analysis crucible used in the inert gas fusion infrared analysis method is a graphite sleeve crucible; and the auxiliary solvent used in the inert gas fusion infrared analysis method is a nickel basket.
Citation Information
Patent Citations
Method for preparing zirconium-based amorphous alloy
CN102080165A
Zirconium-based amorphous alloy and preparation method thereof
CN104498845A
Zr-based amorphous alloy capable of being repeatedly smelted, and preparation method thereof
CN107099757A
Accurate determination method for content of oxygen element in manganese-based alloy
CN112986524A
Method for measuring oxygen content in iron-silicon-aluminum magnetic alloy
CN116359466A
Cited By
Rapid detection and analysis method for oxidation rate of active elements in alloy material
CN121521982A
Method for reducing oxygen content in mother alloy of Y-containing zirconium-based amorphous alloy and preparation method of Y-containing zirconium-based amorphous alloy
CN121826556A